Penerapan Bok Tersier Lepas Sebanding (Knockdown Proportional) pada Tersier Ciranjang DI Cihea, Kabupaten Cianjur - Subari Subari; Muqorrobin Muqorrobin (Balai Teknik Irigasi, 2012)
Irrigation water should be managed by integrating a whole system ( Primary, Secundary and Tertiary canal) shoud be according to plan. Government regulations (PP No. 20, 2006) describe that primary and secondary canal should be managed by government and tertiary canal should be managed by farmer. During tertiary canal management, farmer should be equipped with simple and reliable technology, such as knockdown proportional tertiary box. Tertiary box is one of the most important structures in tertiary canal that divide discharge and deliver it to quarternary and then to the field. This paper described the application of modified tertiary box technology that developed using proportional and knockdown .Proportional design has openings that their width is proportional according to the service area. Thus, this tertiary box can ensure equitable water distribution among fields. Knockdown design make this technology can be easily and quickly installed. This technology applied in Ciranjang tertiary system, Cihea Irrigation Area, Cianjur District. Data collected after construction showed that this tertiary box can deliver equitable discharge (lest then 2% error from planned discharge/ average test Lab and KP.05.), have sufficient mechanical strength (385 kg/cm2), inexpensive construction cost (Rp. 1.446.000,-) and highly acceptable by the farmer.On the way to instal the tertiary box should be carefully in order that appropriate with detail design.